2014
DOI: 10.4172/2161-1068.1000176
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium kumamotonense, another Member of the Mycobacterium terrae Complex Unusually Carrying Two Copies of the Ribosomal RNA Operon

Abstract: The novel slow-grower Mycobacterium kumamotonense was previously misidentified as Mycobacterium tuberculosis complex using commercial probes. Similarly to other slow-growers that cross-react with the tubercle bacilli using commercial probes, M. kumamotonense is carrying two copies of the ribosomal RNA operon (rrn) per genome. Analysis of the corresponding rrn regions allowed the identification of sequences putatively involved in that cross-reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The extra base pair occurs within 20 bp of the 3= end of the sequence in GenBank, while the current sequence with the gap is approximately 80 bp longer (1). Recent studies have shown this species to have two copies of the 16S rRNA gene, and this is the most likely explanation of this single base pair difference (53).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The extra base pair occurs within 20 bp of the 3= end of the sequence in GenBank, while the current sequence with the gap is approximately 80 bp longer (1). Recent studies have shown this species to have two copies of the 16S rRNA gene, and this is the most likely explanation of this single base pair difference (53).…”
Section: Discussionmentioning
confidence: 83%
“…Members of the M. terrae complex are known to harbor two copies of the ribosomal operon that may contain differences in the 16S rRNA gene (52,53), seen as ambiguous bases in sequence electropherograms. Variations in positions of ambiguity were not considered in 16S phylogenetic analyses in this study.…”
Section: Case Reportmentioning
confidence: 99%
“…IS6110 is one of the IS elements which are intensively studied and reported to be specific to M. tuberculosis complex genome. IS6110 is present in multiple copies within the M. tuberculosis genome which makes it an important epidemiological tool for strain identification (Menéndez et al 2014 ; Siddiqui et al 2013 ). The capacity to differentiate between the strains depends on the variation in copy number as well as the insertion sites of IS6110 (Thorne et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, using the restriction fragment length polymorphism (RFLP) pattern of the 16S rDNA gene of M. kumamotonense, it was found that this bacterium carries two copies of the rrn operon per genome [12].…”
Section: Organization Of the Rrna Promotersmentioning
confidence: 99%
“…Previously, it has been described that all mycobacteria have one rrn operon (rrnA) located downstream from the murA gene [9,10]; in addition, other mycobacterial species have a second operon (rrnB) located downstream of the tyrS gene [9,11]. A few mycobacterial species of the Mycobacterium terrae group (MTG), in which M. kumamotonense was also classified, carry two rrn operons per genome [12]. All the same, the sequence and organization of its two previously discovered rrn operons is not yet known.…”
Section: Introductionmentioning
confidence: 99%